2022
DOI: 10.1155/2022/1061274
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effect of Ketamine on Inflammation-Mediated Cytokine Dysregulation in Adults with Treatment-Resistant Depression: Rapid Systematic Review

Abstract: Background. Major depressive disorder (MDD) and treatment-resistant depression (TRD) represent a global source of societal and health burden. To advise proper management of inflammation-related depression among TRD patients, it is important to identify therapeutic clinical treatments. A key factor is related to proinflammatory cytokines such as interleukin-(IL-) 1β, IL-6, and tumor necrosis factor-(TNF-) α which have been implicated in the pathogenesis of depressive symptoms in MDD patients. Ketamine may provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Chronic stress is a major risk factor for MDD and has been associated with increased hypothalamic-pituitary-adrenal (HPA) axis activity and inflammatory activation of immune cells [7]. Increased levels of proinflammatory cytokines in the serum of depressed patients have inspired neuroscientists to investigate the possible role of neuroinflammation in depressive behavior [8]. This ushered in a new era in the neuropsychiatric field, leading to identifying brain immune cells, particularly microglia, as one of the prominent regulators of inflammation in the depressed brain.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic stress is a major risk factor for MDD and has been associated with increased hypothalamic-pituitary-adrenal (HPA) axis activity and inflammatory activation of immune cells [7]. Increased levels of proinflammatory cytokines in the serum of depressed patients have inspired neuroscientists to investigate the possible role of neuroinflammation in depressive behavior [8]. This ushered in a new era in the neuropsychiatric field, leading to identifying brain immune cells, particularly microglia, as one of the prominent regulators of inflammation in the depressed brain.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamines have recently been used more frequently as they are thought to be more immediately effective than antidepressants. In a review entitled "Antidepressant effects of ketamines on inflammation-mediated serotonin dysregulation", ketamine infusions in 5 to 7 studies have notably decreased depression by 50% in 56% of those treated [65]. The effects reputedly involve a reduction in pro-inflammatory cytokines including IL-6 and TNF-1.…”
Section: Sleep Deprivation Shanafimentioning
confidence: 99%
“…Pharmacological studies have also confirmed the interconnection between depression and inflammation. Several antidepressants have been shown to reduce inflammation in both preclinical ( 11 ) and clinical ( 12 , 13 ) models of neuropsychiatric disorders. Antidepressants such as selective serotonin reuptake inhibitors fluoxetine ( 14 ) and paroxetine, tricyclic antidepressants amitriptyline and clomipramine, and monoamine oxidase inhibitors tranylcypromine can prevent LPS-induced microglial changes and the production of inflammatory markers interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%